High Impedance Fault Detection in Power Distribution Networks with Use of Current Harmonic-Based Algorithm - Esmaeil Delroba; Jamal Beiza (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
In very distribution system, physical contact between conductors of a phase and substances around them like trees, walls of the buildings and surfaces below them, always in possible. These conditions known as High Impedance Faults (HIFs), can lead to death due to electricity congestion, burning or ignition via arc or heat of the substances. On the other hand, the whole energy produced by the power company doesn’t achieve by the arbitrary loads and a part of them is lost that this loss is harmful for the power supply companies. Current relaying in distribution systems is only capable of detecting short circuit conditions leads to flowing significant amount of generated electric power to the earth without achieving by the load. It is very difficult to detect HIFs by protection equipments. Because occurrence of them just leads to slight increase in the amount of load current. So it can be considered as a usual increase in the value of load current incorrectly. However various solutions for detecting high impedance faults have been proposed. Most of these approaches are complicated or difficult implementation. In this paper, a novel approach for detecting high impedance faults based on harmonic analysis of current in distribution systems has been presented. Various simulations in PSCAD envirounment have validated that proposed approach in simple in implementation and have great accuracy.